2002
DOI: 10.1128/aem.68.4.1743-1753.2002
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Airborne Fungi in Buildings and Outdoor Environments in the United States

Abstract: We examined 12,026 fungal air samples (9,619 indoor samples and 2,407 outdoor samples) from 1,717 buildings located across the United States; these samples were collected during indoor air quality investigations performed from 1996 to 1998. For all buildings, both indoor and outdoor air samples were collected with an Andersen N6 sampler. The culturable airborne fungal concentrations in indoor air were lower than those in outdoor air. The fungal levels were highest in the fall and summer and lowest in the winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
448
6
26

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 584 publications
(537 citation statements)
references
References 21 publications
57
448
6
26
Order By: Relevance
“…Moreover, Penicillium was the only frequently occurring genus in our study showing a significant association with visible mold and somewhat weaker associations with visible water and musty/ moldy odor. Penicillium also exhibited higher indoor than outdoor levels in our study, an observation reported by others throughout the United States (Shelton et al, 2002;Chew et al, 2003;O'Connor et al, 2004). The ubiquitous nature of Penicillium sp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, Penicillium was the only frequently occurring genus in our study showing a significant association with visible mold and somewhat weaker associations with visible water and musty/ moldy odor. Penicillium also exhibited higher indoor than outdoor levels in our study, an observation reported by others throughout the United States (Shelton et al, 2002;Chew et al, 2003;O'Connor et al, 2004). The ubiquitous nature of Penicillium sp.…”
Section: Discussionsupporting
confidence: 84%
“…Mold levels tend to be highest in the summer and fall throughout the United States (Shelton et al, 2002), and were observed in this project as well. Children born in the summer and those with fall mold collection dates, an overlapping group in our study, were at an increased risk of wheeze in unadjusted logistic regression models.…”
Section: Discussionsupporting
confidence: 71%
“…In outdoor environment, the non-sporulating fungi (81.1%) was the predominant type followed by Cladosporium (70.0%), Penicillium (60.0%), Aspergillus (43.3%), Alternaria (24.4%) and Yeast (13.3%). The predominant culturable fungi reported in this study are consistent with previous studies (Ren et al, 1999;Shelton et al, 2002;Adhikari et al, 2005). Indoor and outdoor environments revealed exactly the same frequency of 81.1% of non-sporulating culturable fungi, which may be originated from Ascomycetes and Basidiomycetes.…”
Section: Indoor and Outdoor Concentration Of Culturable Fungisupporting
confidence: 92%
“…E.g., the median levels of indoor and outdoor culturable fungi in 80 homes in Latrobe Valley, Australia were 812 and 1042 CFU m -3 , respectively (Garrett et al, 1997). The median indoor and outdoor concentrations of 1717 buildings located across the United States were 82 and 540 CFU m -3 , respectively (Shelton et al, 2002). In addition, a study conducted in Greater New Haven, Connecticut revealed higher mean levels of culturable fungi (Ren et al, 1999) than found in the present study.…”
Section: Indoor and Outdoor Concentration Of Culturable Fungicontrasting
confidence: 62%
See 1 more Smart Citation